Similar ratio experiment and characteristic analysis of quasi-sandstone - Yan, Lianghuan; Chang, Jucai; Qiao, Longquan; Shi, Wenbao; Wang, Tuo; Pang, Dongdong; Li, Yuan; Guo, Yijun (Frontiers in Earth Science, 2023)
The stability control of surrounding rock in deep roadway is becoming more and more difficult, and grouting reinforcement support has become the mainstream of roadway control. In order to obtain the ratio of quasi-sandstone material corresponding to the grouting body, this paper uses river sand as aggregate, cement and gypsum as cementing agent, retarder and defoamer as additives, and carries out orthogonal proportioning tests with three influencing factors: water-binder ratio (ratio of water to mass of cementing agent), gypsum-cement ratio (ratio of gypsum to mass of cement) and binder-aggregate ratio (ratio of cementing agent to aggregate mass), and compares and analyzes the sensitivity of each factor on the density, compressive strength, tensile strength, elastic modulus, Poisson's ratio, longitudinal wave velocity, elasticity index and brittleness index of quasi-sandstone material. The results show that (1) the Water-binder ratio has the greatest effect on the sensitivity of material compressive strength, tensile strength, elastic modulus, Poisson's ratio and longitudinal wave velocity; the gypsum-cement ratio has the greatest effect on the sensitivity of material deformation index and brittleness index; the binder-aggregate ratio has the greatest effect on the sensitivity of material density. (2) Reducing the Water-binder ratio can improve the density, compressive strength and tensile strength of the material; reducing the paste ratio can improve the modulus of elasticity, Poisson's ratio and longitudinal wave speed of the material; as the gypsum-cement ratio increases, the deformation index first decreases and then increases and then decreases; as the binder-aggregate ratio increases, the brittleness index first increases and then decreases and then increases. (3) The empirical equations between physical and mechanical properties of sandstone-like materials and Water-binder ratio, gypsum-cement ratio and binder-aggregate ratio were established based on multiple linear regression analysis, and more reasonable material ratios were quickly obtained by physical and mechanical parameters of materials. The results of the study provide theoretical references for similar material simulation tests for quasi-sandstone grouting.